2017
DOI: 10.1136/tobaccocontrol-2017-053881
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Natural American Spirit advertising on current and former smokers’ perceptions and intentions

Abstract: The findings of this study provide causal support for the need for further regulatory action to address the potentially harmful ramifications of claims used in NAS advertising.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…It is also possible that the manipulations used in Study 1 were not strong enough to prompt meaningful reactions to influence beliefs, nor meaningful emotional responses. Second, the established eight-item belief scale was employed because it was previously validated as a misinformation measure in this specific context (Gratale et al, 2018). However, only some of the specific belief items within this scale were directly related to the messages explicitly appearing in the stories.…”
Section: Study 1 Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also possible that the manipulations used in Study 1 were not strong enough to prompt meaningful reactions to influence beliefs, nor meaningful emotional responses. Second, the established eight-item belief scale was employed because it was previously validated as a misinformation measure in this specific context (Gratale et al, 2018). However, only some of the specific belief items within this scale were directly related to the messages explicitly appearing in the stories.…”
Section: Study 1 Discussionmentioning
confidence: 99%
“…Beliefs were measured with eight Likert-type items on a 8-point scale, anchored by strongly disagree to strongly agree (M = 4.34, SD = 1.49, α = .94), that was validated by a previous study (Gratale, Maloney, Sangalang, & Cappella, 2018). Items were averaged.…”
Section: Misinformed Beliefsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of experimental studies have established that "organic" or "additive-free" descriptors decrease tobacco harm perceptions. [1][2][3][4][5] Two nationally representative studies have shown that Natural American Spirit (NAS) smokers specifically misunderstand the relative harm of their brand, which uses the "organic" descriptor on some products and, until late 2017, used the "additive-free" descriptor on its cigarette sub-brands. 6,7 However, the overall prevalence of belief that "organic" and "additive-free" tobacco products are less harmful than regular tobacco products has not been reported in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…When consumers read that e-cigarettes are natural, they might assume that the known risks associated with smoking are natural too ( McDaniel & Malone, 2007 ; Swanson, 1977 ) much like drowning is a risk associated with swimming. In the past, tobacco companies have engaged in similar misleading marketing practices to promote tobacco and menthol products by claiming they could produce fresh and natural sensations ( Anderson, 2011 ; Baig, Byron, Lazard, & Brewer, 2018 ; Epperson, Henriksen, & Prochaska, 2017 ; Gratale, Maloney, Sangalang, & Cappella, 2017 ; Moran, Pierce, Weiger, Cunningham, & Sargent, 2017 ). If there is systematic evidence that healthy food terms are now being used in advertising to promote e-cigarettes, then such marketing practices would be a potential subject for U.S. Food and Drug Administration (FDA) regulation.…”
Section: Introductionmentioning
confidence: 99%